Delayed Tuberculosis Treatment in Urban and Suburban Ontario - Andrea S Gershon; Wendy Wobeser; Jack V Tu (Canadian Respiratory Journal)
BACKGROUND: Delay in the treatment of patients with tuberculosis (TB) increases the risk of poor clinical outcomes – including death and transmission of disease – and may be reducible.